Cloning, purification and characterisation of cytosolic fructose-1, 6-bisphosphatase from mung bean (Vigna radiata). (15th June 2021) - Chen, Lin; Zhao, Xue; He, Yun; Yang, Hongshun
Highlights: The cytosolic fructose-1, 6-bisphosphatase was cloned from mung bean. The replacement of Met 251 by Leu improved the substrate affinity and activity. The mutants of AMP binding sites revealed their connections with active center. Abstract: To improve the crop yield and quality, the cytosolic fructose-1, 6-bisphosphatase (cFBPase) from mung bean ( Vigna radiata ), a rate-limiting enzyme in gluconeogenesis, was cloned, purified, and structurally characterised. To function it required Mg 2+ and Mn 2+ at 0.01–10 mM. The Michaelis-Menton constant and adenosine monophosphate (AMP) inhibitory constant ( Ki ) were 7.96 and 111.09 μM, respectively. The functional site residues of AMP binding (Arg 30, Asp 32, and Phe 33 ) and the active site residues (Asn 218 and Met 251 ) were tested via site-directed mutagenesis and molecular docking. Asn 218 and Met 251 were replaced by Tyr and Leu, respectively. The M251L mutant showed enhanced substrate affinity and activity, resulting from decreased binding energy (–2.58 kcal·mol −1 ) and molecular distance (4.2 Å). AMP binding site mutations changed the enzyme activities, indicating a connection between the binding and active sites. Furthermore, Ki and docking analysis revealed that Asp 32 plays a key role in maintaining the AMP binding conformation.